Leachability of mercury in coal fly ash from coal-fired power plants in southwest China - Huang, Yiming; Liu, Jinling; Wang, Guan; Wang, Qingfeng; Zeng, Boping; Xiao, Zhongjiu; Sun, Guangyi; Li, Zhonggen (Frontiers in Environmental Science, 2022)
Mercury (Hg)-laden coal fly ash is an environmental concern when it is exposed to precipitation or surface/groundwater under natural conditions. In this study, fly ash samples collected from fifteen coal-fired power plants (CFPPs) in Guizhou province of southwest China were subjected to examine the different Hg binding forms. The results showed that total Hg in fly ash from these CFPPs ranged from 30 to 870 ng/g. The percentage of different Hg binding forms in coal fly ash decreased in the follow-ing order: strong complexed form (64%–91%) > acid-soluble form (1%–25%) and sul-fide form (3.4%–14.8%) > ion-exchangeable form (0.01%–8.1%), and water-soluble form (0.01%–4.4%). The low proportion of water-soluble and ion-exchangeable forms indicated that Hg was not easily removed under natural conditions. Furthermore, fly ash samples from three out of fifteen CFPPs were carried out the leaching experiments to disclose the leachability of Hg and the transmedia migration potential of this ele-ment. The results indicated pH dependence of Hg leachability, with more than 4-times fold higher Hg been leached out under acidic (pH < 5.5) and strong alkaline (pH > 13) conditions than under neutral and weakly alkaline conditions (pH = 7–12). In addition, Hg was leached out more in higher liquid/solid ratio than lower ratios. Nevertheless, Hg concentration in extract (< 7 ng/L) of these three CFPPs under all conditions was well below the applicable regulation limits, and less than 0.11% of total Hg was leached out. This study demonstrated that Hg in the CFPP fly ashes was more stable under natural conditions when exposed to surface/groundwaters and had a negligible Hg leachability.